2021
DOI: 10.3390/life11070712
|View full text |Cite
|
Sign up to set email alerts
|

The Value of OCT and OCTA as Potential Biomarkers for Preclinical Alzheimer’s Disease: A Review Study

Abstract: Preclinical Alzheimer’s disease (AD) includes cognitively healthy subjects with at least one positive biomarker: reduction in cerebrospinal fluid Aβ42 or visualization of cerebral amyloidosis by positron emission tomography imaging. The use of these biomarkers is expensive, invasive, and not always possible. It has been shown that the retinal changes measured by optical coherence tomography (OCT) and OCT-angiography (OCTA) could be biomarkers of AD. Diagnosis in early stages before irreversible AD neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Neuropsychological assessments such as the MoCA is a fundamental approach that is used to assess the cognition in individuals. The association between OCTA variables and the MoCA has been suggested to be useful in the clinical evaluation and monitoring of patients with cognitive dysfunction ( Zhang et al, 2020 ; López-Cuenca et al, 2021 ). Our current report showed that the MoCA scores significantly correlated with SVC changes in aging individuals, which are congruent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological assessments such as the MoCA is a fundamental approach that is used to assess the cognition in individuals. The association between OCTA variables and the MoCA has been suggested to be useful in the clinical evaluation and monitoring of patients with cognitive dysfunction ( Zhang et al, 2020 ; López-Cuenca et al, 2021 ). Our current report showed that the MoCA scores significantly correlated with SVC changes in aging individuals, which are congruent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nuclear imaging modalities have some disadvantages, such as high cost, poor resolution, long testing times, and unavoidable exposure to radioactivity (Xu et al ., 2016 ). Optical imaging modalities, particularly NIRF imaging, may provide a non-invasive in vivo method to visualize the real-time status of the AD brains more accurately at the biomolecular level (Liu et al ., 2021b ; López-Cuenca et al ., 2021 ). Importantly, small molecule NIR probes are used to detect Tau protein, β-amyloid, and other biomarkers (Rai et al ., 2022 ).…”
Section: Fluorescence Molecular Tomographymentioning
confidence: 99%
“…A systematic review of 71 studies such as this found that while AD patients often exhibit retinal thinning on OCT retinal scans, the literature lacks sufficient evidence on the specific areas of the retina that undergo changes [15]. Another review of 64 studies focusing on biomarker identification using OCT in patients with AD concluded that a very limited number of studies analyze patients with preclinical AD or are longitudinal, arguing that conducting studies following the evolution of preclinical AD patients would be of great value [16]. These identified gaps in the literature motivate a longitudinal study of retinal layer changes in AD patients.…”
Section: Introductionmentioning
confidence: 99%